STRUCTURAL PHASE STATE AND TRIBOTECHNICAL PROPERTIES OF CASTINGS FROM HIGH-CHROME STEEL 20Cr15Mn3, OBTAINED BY TECHNOLOGY OF PRECISION SOL-GEL CASTING IN CERAMIC FORMS - V. A. Kukareko; A. N. Grigorchik; E. V. Astrashab; P. E. Lushchik (Литьë и металлургия, 2018)
The structure, phase composition and tribotechnical properties of the impeller casting for oil and centrifugal pumps made from high-chromium steel 20Cr15Mn3, obtained by the technology of precise casting, were studied. It was concluded that impeller casting made from high-chromium steel 20Cr15Mn3, obtained by the technology of exact casting of Sol-Gel in ceramic molds, had improved properties and can serve as a replacement for the traditionally used material – cast iron.